(3GdJONd GdYScQj GdCeQjcj aj CaZGfSJGf (B/ s - (3YHOGdQDha MHjH Gddg YHOGdMejOs; (3CMeO CHhGdhaG s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3JJeMhQ GdQSGdI Mhd GdbhGYO GdbGfhfjI GdOhdjI aj GdJONd GdYScQj GdCeQjcj aj CaZGfSJGf (B: (3aLGAJ eTJedI Ydj aUd JegjOj h CQHY aUhd CNQi (B: (3jJVef aUd JegjOj GdYhGed GdLZQGajI h GdJGQjNjI ddJONd GdYScQj aj CaZGfSJGf h LZQGajI CaZGfSJGf h JCKjQgG Ydi YdGbJgG GdOhdjI h XghQ JfXje GdbGYOI h fTCI WGdHGf h ehba GdeLJeY GdOhdi efgeG h fTCI GdEQgGH aj CaZGfSJGf h NWhQI GdEQgGH GdOhdj Ydi GdSde h GdCef GdOhdjjf (B: (3h bO JVef GdaUd GdChd GdJONd GdOhdi aj TFhf Ohd (B: (3Ydi Mjf JfGhd GdaUd GdKGfj eHOC YOe eTQhYjI GdJONd aj VhA CMcGe GdbGfhf GdOhdjs
(3jTJed Ydi edGMb(B: (3UaMI (B261-267s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2013s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B270-294s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3GdJONd GdYScQjs; (3YOe eTQhYjI GdJONds; (3fTCI GdEQgGHs; (3fTCI GdGQgGH aj CaZGfSJGfs; (3GfJgGcGJ eHOG YOe eTQhYjI GdJONds; (3eaghe GdJONd aj Gdabg GdOhdjs; (3GdGSGS GdbGfhfi dbQGQGJ eLdS GdGefs; (3GaZGfSJGfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs